Sofyan Syafri Harahap's Thoughts on Sharia Accounting and Its Implementation - Abdul Hakim; Ahmad Riyansyah (AT-TAFAHUM: Journal of Law, 2017)
This study examines Sofyan Syafri Harahap's thoughts on Sharia Accounting and its urgency in contemporary accounting practices. The study is based on the criticism of conventional accounting, which is considered unable to fully guarantee justice, transparency, accountability, and truthfulness in financial reporting. Conventional accounting is often viewed as being influenced by capitalist ideology, emphasizing profit maximization and material interests while neglecting ethical and spiritual dimensions. According to Sofyan Syafri Harahap, accounting should not merely function as a tool for decision-making but also as a means of accountability to stakeholders and ultimately to Allah SWT. The study reveals that the concept of Sharia Accounting is rooted in Islamic teachings, particularly in the principles of justice, honesty, transparency, and accountability as reflected in the Qur’an, especially Surah Al-Baqarah verse 282. Sharia Accounting seeks to ensure that financial information is free from fraud, manipulation, and injustice while promoting ethical economic activities. Sofyan Syafri Harahap argues that Islamic accounting existed conceptually long before the emergence of conventional accounting introduced by Luca Pacioli and that accounting practices should be aligned with Islamic values and objectives.